Reason, Will and Emotion - Crittenden, P. author. aut Link
IX, 266 p.
Keywords: This powerful exploration of an important topic in philosophy of mind from ancient to contemporary philosophy presents an original argument against the current direction of debate and examines a wide range of philosophers from both continental and analytic traditions.